The 'Best Available Science' and the Paris Agreement on Climate Change. (March 2016) - Hanekamp, Jaap C.; Bergkamp, Lucas
Abstract : Recognising the importance of science to climate policies, the Paris Agreement on Climate Change (the 'Paris Agreement' or 'Agreement') stipulates that 'an effective and progressive response to the urgent threat of climate change' should be based on 'the best available scientific knowledge.' The terms 'best available scientific knowledge' or 'best available science' are used in several places throughout the agreement.